Innovation and Resilience in Philippine Cities: Post-Pandemic Economic Performance Through the CMCI Framework - Estillore, Denmichael Neil C.; Medalla, Jerelyn B. (Universitas Muhammadiyah Yogyakarta, 2026)
This study assesses how innovation and resiliency, as measured through the City and Municipality Competitiveness Index (CMCI) framework, affect the Philippine Cities’ post-pandemic economic performance. A panel-corrected standard error regression analysis was employed to analyze data from 146 Philippine cities covering the period from 2022 to 2024. Findings show that innovation exert significant positive effect on economic performance. Specifically, intellectual property registration and internet services significantly increase LSIR, confirming the importance of digital access and knowledge-based growth. Conversely, startup facilities revealed a negative association, likely due to high operational costs and underdeveloped ecosystems in Philippine cities. Moreover, findings show that resiliency have significant negative effect on economic performance. This is likely due to costly resiliency projects that may misallocate resources, thereby burdening fiscal capacity and local economy. Additionally, resiliency sub-indicators such as land-use planning, disaster planning, and utilities can significantly enhance economic performance. However, excessive complexity and high costs for these may strain fiscal budgets and hinder local economies. Emergency infrastructure, early warning systems, and resilience-related employed population showed a negative effect due to high upfront costs and resource diversion from revenue-generating activities. Furthermore, promoting innovation and implementing efficient resilience strategies without straining local revenues are necessary for Philippine cities towards sustainable post-pandemic recovery.